HUBUNGAN KECERDASAN EMOSIONAL DENGAN PENYESUAIAN SOSIAL SISWA AKSELERASI DI MAN BANYUWANGI - Jon Iskandar Bahari (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2015)
Individuals in everyday life are required to establish a relationship with another individual. Through this socialization process, individuals make adjustments with the surrounding environment. To establish a good relationship, an individ ual is required to have good intelligence emosianal. Basi cally between emotional intelligence and social adjustment interconnected. Emotional intelligence is a subset of social intelligence that involves the ability to monitor feelings and emotions well in ourselves and in others. This study aims to determine how the intelligence level of students emosianal acceleration, how the level of students’ social adjustment of acceleration, and learns of the relationship of emotional intelligence and social adjustment in students acceleration MAN Banyuwangi. This study uses a quantitative correlation with research subjects students of class X MAN accel eration Banyuwangi totaling 214 students, while 31 of them designated as a sample. Keywords :